The Role of Teaching Materials in Islamic Religious Education and Its Function in Forming Students' Critical Attitudes - Ahmad Nabriz; Ahmad Faizal Syahrul Azmi; Abubaker Kashada; Rahmat Ullah; Ajoy Chandra (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This research aims to evaluate the role of teaching materials in Islamic Religious Education (PAI) and their function in forming students' critical attitudes. Effective teaching materials are an important component in the educational process, which not only conveys religious knowledge but also encourages students to think critically and reflectively. The research approach used is qualitative, with data collection techniques through observation, interviews with teachers and students, as well as analysis of teaching materials used in the PAI curriculum. The research results show that well-designed teaching materials, which include reflective questions, case studies, and open discussions, are able to encourage students to develop a critical attitude. However, challenges in implementing these teaching materials include a lack of training for teachers in using teaching materials effectively and limited teaching materials available. Therefore, it is recommended to improve the quality and availability of teaching materials and provide ongoing training for teachers to maximize the potential of teaching materials in forming students' critical attitudes. Thus, PAI teaching materials can be more effective in developing students' critical thinking skills and strengthening their understanding of religious values.